Enhancing Quality Education through Comprehensive Teacher Education : A Systematic Review of Literature - Badriya, Ambu-Saidi; Fung, Chorng Yuan; Kristina, Turner; Agnes Lim, Siang Siew (Universiti Teknologi MARA, 2024)
This paper presents a systematic literature review (SLR) focusing on the pivotal role of teacher education in achieving Sustainable Development Goal 4 (SDG 4), which emphasizes inclusive and equitable quality education for all. The review synthesizes key themes emerging from a thorough analysis of selected research articles, highlighting areas such as evaluation and assessment in teacher education, innovative teaching approaches, continuous professional development, student-centered learning, feedback and assessment practices, teacher perceptions and support systems, and policy implications and educational reforms. The analysis procedure involved a rigorous thematic analysis of the selected literature, where the data were coded, categorized, and synthesized into seven critical themes. Each theme was examined in-depth, drawing on empirical evidence and theoretical perspectives to provide a comprehensive understanding of how teacher education contributes to the broader goals of inclusivity, equity, and quality in education. The findings offer valuable insights for educators, policymakers, and researchers aiming to enhance educational practices and outcomes.